2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--23059
|View full text |Cite
|
Sign up to set email alerts
|

Student Use of Design Ethnography Techniques during Front-end Phases of Design

Abstract: is currently a Ph.D. candidate in mechanical engineering at the University of Michigan. His research focuses on the design of medical devices for resource limited settings, particularly related to the use of design ethnography in developing these technologies. He received his B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Engineering education often lacks proper training in front-end design work, and thus students have been shown to struggle with front-end design activities. Students have been found to undervalue stakeholder engagements (Mohedas et al 2020), fixate on the use of high-fidelity prototypes (Mathias et al 2018), inadequately implement ethnography techniques (Mohedas, Daly & Sienko 2014), and are not likely to associate prototype development to quality of final design outcomes (Nelson & Menold 2020). These practices do not align with recommendations from the literature and result in superficial design outcomes.…”
Section: Tools and Training For Remote Stakeholder Engagementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineering education often lacks proper training in front-end design work, and thus students have been shown to struggle with front-end design activities. Students have been found to undervalue stakeholder engagements (Mohedas et al 2020), fixate on the use of high-fidelity prototypes (Mathias et al 2018), inadequately implement ethnography techniques (Mohedas, Daly & Sienko 2014), and are not likely to associate prototype development to quality of final design outcomes (Nelson & Menold 2020). These practices do not align with recommendations from the literature and result in superficial design outcomes.…”
Section: Tools and Training For Remote Stakeholder Engagementsmentioning
confidence: 99%
“…These practices do not align with recommendations from the literature and result in superficial design outcomes. The gaps between student behavior and the practices recommended for front-end design highlight the need for improvements to engineering education (Mohedas et al 2014). There is also a lack of educational support for engineering students regarding remote design.…”
Section: Tools and Training For Remote Stakeholder Engagementsmentioning
confidence: 99%
“…However, prior research has shown that students do not always interact with stakeholders successfully (Mohedas, Daly, & Sienko, 2015;Scott, 2008;Sugar, 2001). For example, in design course projects, students have been shown to struggle navigating ambiguous information, analyzing qualitative data, and identifying what stakeholder information is important to their design decisions (Mohedas et al, 2014a(Mohedas et al, , 2014b(Mohedas et al, , 2014c. Other studies have highlighted challenges students have encountered during stakeholder interviews, such as ensuring that critical topics are covered during the interview; asking appropriate questions; uncovering how stakeholders think or feel about certain topics; and obtaining information about social, political, and cultural factors that may affect design decisions (Burnay, Jureta, & Faulkner, 2014;Donoghue, 2010;Goguen & Linde, 1993;Wetherbe, 1991).…”
Section: Student Engagement With Stakeholdersmentioning
confidence: 99%
“…Stakeholder engagement often results in a large amount of data (Beyer & Holtzblatt, 1998;Sachidanandam & Gill, 2008), and studies have shown that during a design course students may shift away from a human-centered view of design if the complexity of gathering and synthesizing multiple diverse perspectives from stakeholders during decision-making proves too burdensome (Mohedas et al, 2014a;Scott, 2008). In one study, although most student designers acknowledged the benefits of incorporating stakeholders' input into front-end design processes, they encountered obstacles while doing so and often interacted with stakeholders in a superficial manner (Mohedas et al, 2014a(Mohedas et al, , 2014c. Another study of novices and experts performing a design task found that novices spent less time than experts in gathering information (Atman et al, 2007).…”
Section: Student Engagement With Stakeholdersmentioning
confidence: 99%
“…Here, prototypes can help designers develop deep understandings of stakeholders’ needs and wants (Skaggs 2010) by providing a fundamentally different way of collaborating through a ‘shared space’ that enables conversations between participants and designers (Schrage 1999). Well-planned communication is particularly crucial during the early stages of a design project when both the problem and solution spaces are undefined, and comprehensive information can be difficult to collect (Mohedas, Daly & Sienko 2014). For example, in a project described by Sarvestani & Sienko (2014), the designers initially attempted to establish requirements for an adult male circumcision device from stakeholders in Uganda without the use of prototypes, but were more successful once they introduced prototypes, particularly with respect to eliciting cultural and other contextual factors.…”
Section: Introductionmentioning
confidence: 99%